2020
DOI: 10.14719/pst.2020.7.2.714
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening of two Ilam native plants Ziziphus nummularia (Burm.f.) Wight & Arn. and Ziziphus spina-christi (Mill.) Georgi using HS-SPME and GC-MS spectroscopy

Abstract: Essential oils are aromatic compounds widely used in the perfumery, pharmaceutical and food industries. There are several methods to extract essential oils and extracts. These methods include distillation, pressure or scraping, pressing and razor technique, headspace solid-phase micro extraction (HS-SPME), solvent extraction, extraction by bioactive hydrolyzing enzymes, and CO2 extraction. The aim of this study was to investigate the amounts of active ingredients of essential oils of medicinal plants Ziziphus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Helium (49.6 psi) was used as carrier gas at a flow rate of 1 mL/min which propelled the compounds and also act as reagent gas that causes charge-exchange chemical ionization of the analytes which are then separated on the basis of mass-to-charge ( m/z ) ratios. These components are then identified through comparison with known standards in literature [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Helium (49.6 psi) was used as carrier gas at a flow rate of 1 mL/min which propelled the compounds and also act as reagent gas that causes charge-exchange chemical ionization of the analytes which are then separated on the basis of mass-to-charge ( m/z ) ratios. These components are then identified through comparison with known standards in literature [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The identification of major constituents of essential oil was done by comparison of their retention times and retention indices with those of authentic compounds reported in the literature. The essential oil components were identified by comparing their retention indices and mass spectral fragmentation patterns the compounds present with those reported in the Wiley and NIST libraries, mass spectral library, and also with mass spectral data reported in the literature [ 20 , 21 ]. Kovats retention indices were also determined using formula: …”
Section: Methodsmentioning
confidence: 99%
“…A summary of other polyphenolic compounds isolated/detected in Z. spina are presented in Table 2 and Figure 3 . Using head space solid-phase microextraction (HS-SPME) and GC-MS methods, identification of α -pinene, β -pinene, β -myrcene, β -phellandrene, L-menthone, carane, trans-caryophyllene, and bicyclogermacrene was achieved as the major constituents of the essential oils of Ziziphus spina-christi [ 180 ]. Odeh et al [ 181 ] reported the presence of benzaldehyde, phenylacetyldehyde, phenylethylalcohol, benzene, acetonitrile, 2-ethyl hexanoic acid, octanoic acid, 2-methoxy-4-(1-propanol)-6-acetate phenol, nonanoic acid, decanoic acid, 1-hydroxy-2,4,6-trimethylbenzene, and 5-hydroxymethyl-2-furan carbonyldehyde in honey obtained from Z. spina using HS-SPME-GC-MS methods.…”
Section: Resultsmentioning
confidence: 99%
“…In Iranian herbal medicine, many medicinal plants are used to treat various disorders and diseases. One of the most important reasons for the effectiveness of medicinal plants is the presence of effective medicinal substances ( Solati et al ., 2021 ; Bahmani et al ., 2020 ; Aidy et al ., 2020 ; Karimi et al ., 2019 ; Abbasi et al ., 2016 ; 2020 ). The effect of medicinal plants on sperm production and testosterone is due to the presence of secondary medicinal compounds.…”
Section: Discussionmentioning
confidence: 99%